Whey protein with potassium bicarbonate supplement attenuates the reduction in muscle oxidative capacity during 19 days of bed rest - Bosutti, Alessandra; Salanova, Michele; Blottner, Dieter; Bühlmeier, Judith; Mulder, Edwin; Rittweger, Jörn; Yap, Moi Hoon; Ganse, Bergita; Degens, Hans (Journal of Applied Physiology)
The effectiveness of whey protein plus potassium bicarbonate-enriched diet (WP+KHCO 3 ) in mitigating disuse-induced changes in muscle fiber oxidative capacity and capillarization was investigated in a 21-day crossover design bed rest study. Ten healthy men (31 ± 6 yr) once received WP+KHCO 3 and once received a standardized isocaloric diet. Muscle biopsies were taken 2 days before and during the 19th day of bed rest (BR) from the soleus (SOL) and vastus lateralis (VL) muscle. Whole-body aerobic power (V̇o 2 max ), muscle fatigue, and isometric strength of knee extensor and plantar flexor muscles were monitored. Muscle fiber types and capillaries were identified by immunohistochemistry. Fiber oxidative capacity was determined as the optical density (OD) at 660 nm of succinate dehydrogenase (SDH)-stained sections. The product of fiber cross-sectional area and SDH-OD (integrated SDH) indicated the maximal oxygen consumption of that fiber. The maximal oxygen consumption supported by a capillary was calculated as the integrated SDH in its supply area. BR reduced isometric strength of knee extensor muscles ( P < 0.05), and the fiber oxidative capacity ( P < 0.001) and V̇o 2 max ( P = 0.042), but had no significant impact on muscle capillarization or fatigue resistance of thigh muscles. The maximal oxygen consumption supported by a capillary was reduced by 24% in SOL and 16% in VL ( P < 0.001). WP+KHCO 3 attenuated the disuse-induced reduction in fiber oxidative capacity in both muscles ( P < 0.01). In conclusion, following 19 days of bed rest, the decrement in fiber oxidative capacity is proportionally larger than the loss of capillaries. WP+KHCO 3 appears to attenuate disuse-induced reductions in fiber oxidative capacity.
Keywords: Physiology (medical); Physiology

High sodium chloride intake exacerbates immobilization-induced bone resorption and protein losses - Frings-Meuthen, Petra; Bühlmeier, Judith; Baecker, Natalie; Stehle, Peter; Fimmers, Rolf; May, Francisca; Kluge, Goetz; Heer, Martina (Journal of Applied Physiology)
We examined, in immobilization, the effect of a diet high in sodium chloride (NaCl) on bone markers, nitrogen balance, and acid-base status. Eight healthy male test subjects participated in a 14-day head-down-tilt bed rest (HDBR) study. During the bed rest period they received, in a randomized crossover design, a high (7.7 meq Na + /kg body wt per day) and a low (0.7 meq Na + /kg body wt per day) NaCl diet. As expected, 24-h excretion of urinary calcium was significantly greater in the high-NaCl-intake HDBR phase than in the low-NaCl-intake HDBR phase ( P < 0.001). High NaCl intake caused a 43–50% greater excretion of the bone resorption markers COOH- (CTX) and NH 2 - (NTX) terminal telopeptide of type I collagen in HDBR than low NaCl in HDBR (CTX/NTX: P < 0.001). Serum concentrations of the bone formation markers bone-specific alkaline phosphatase (bAP) and NH 2 -terminal propeptide of type I procollagen (PINP) were identical in both NaCl intake phases. High NaCl intake led to a more negative nitrogen balance in HDBR ( P < 0.001). Changes were accompanied by increased serum chloride concentration ( P = 0.008), reduced blood bicarbonate ( P = 0.017), and base excess ( P = 0.009) whereas net acid excretion was lower during high than during low NaCl intake in immobilization ( P < 0.001). High NaCl intake during immobilization exacerbates disuse-induced bone and muscle loss by causing further protein wasting and an increase in bone resorption. Changes in the acid-base status, mainly caused by disturbances in electrolyte metabolism, seem to determine NaCl-induced degradation processes.
Keywords: Physiology (medical); Physiology